The Ogoki River Guides : Emergent Leadership among the Northern Ojibwa - Hedican, Edward J. (Book collections on Project MUSE., 2006)
The Ogoki River Guides describes the prolonged struggle that members of a small native community in northern Ontario have undertaken in their attempt to establish a viable local economy. The leaders of Collins, the community in which the events of the book take place, have made a concerted effort to ensure that the community takes charge of its own affairs and in doing so have generated some important lessons for governmental policy in northern areas. The study makes evident the fact that certain changes in current government practices are needed, especially in areas of local inputs i.